Quantifying ocular microcirculation in hypertension patients with carotid artery stenosis - Ma, Jinlan; Gelie, NanJia; Zhu, Mingjuan; Ma, Xiaolu; Han, Changjing (Frontiers in Neuroscience, 2024)
Background Carotid artery stenosis (CAS) is one of the most common macrovascular complications of hypertension. however, the effect of CAS on ocular microcirculation had not been quantified in hypertension patients. The aims of this study were to quantify ocular microcirculation metrics in hypertension with CAS patients and to explore the relationship between micro-and macroangiopathy of hypertension. Methods All participants(community-based) underwent detailed assessments including carotid ultrasonography, optical coherence tomography angiography (OCTA) and enhanced depth imaging (EDI)-OCT. CAS was diagnosed by carotid ultrasonography. Retinal microcirculation metrics including vessel density (VD), skeleton density (SD), fractal dimension (FD) and foveal avascular zone (FAZ) were quantified by OCTA and ImageJ software. Choroidal microcirculation metrics including subfoveal choroidal thickness (SFCT), luminal area (LA) and choroidal vascularity index (CVI) were quantified by EDI-OCT and ImageJ. Retinal vessel caliber metrics including central retinal artery equivalent (CRAE), central retinal vein equivalent (CRVE) were calculated by revised formulas. Above metrics were compared among hypertension with CAS group (HCAS), hypertension with no CAS group (HNCAS) and healthy control group. Results In comparison of HCAS versus HNCAS group, retinal metrics including VD, SD, FD and choroidal metrics including CVI, LA were significantly decreased in HCAS group (all P<0.05), however, FAZ, SFCT and retinal vessel caliber metrics including CRAE, CRVE and AVR were comparable between groups (all P>0.05). In comparison of HNCAS and healthy control group, VD, SD and CRAE, AVR were significantly decreased in HNCAS group (all P<0.05), meanwhile, choroidal metrics were comparable between groups (all P>0.05). Liner regression analyses showed that intima media thickness (IMT)(P=0.01) and peak systolic velocity (PSV)(P=0.002) were negatively related to retinal VD in hypertension patients. Logistic regression analyses disclosed that older age(P<0.001), smoking history (P=0.002), lower VD(P=0.04), SD(P=0.02) and CVI(P<0.001) were related to the presence of CAS in hypertension patients. Conclusions CAS in hypertension induced hypoperfusion in ocular microcirculation, and the decreased retinal VD and choroidal CVI were significantly associated with the presence of CAS in hypertension, suggesting that hypertension macro-and microangiopathy were mutual effected and share the common pathophysiology. Furthermore, OCT is a useful tool to assess hypertension patient's CAS risk profile by a non-invasive way.